MAXILLARY SINUSITIS AS A CAUSE OF SECRETORY OTITIS MEDIA IN CHILDREN IN HAZARA DIVISION - Ghani, Rehman; Nabi, Ghulam (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT Secretary otitis media, Nousuppastive otitis media, Glue ears, otitis media with effusion Different means of the same problem. Secretary otitis media is one of the common causes of Deafness in children in this part of the world. Secretary otitis media is due to development of negative pressure inside the middle ear earnity because of Eustachian tube obstruction with intact tynpanic membrane. This negative pressure sucks the fluid from the Surrounding Blood vessels replacing the vacuum of the middle ear with fluid. This fluid is responsible for Deafness. 'The obstruction of the Evstachrain tube is due its edema. The causes blamed to be responsible for this Edema areallesgies, Jnlarged Aduoids, and postnasal Discharge. This ostuasal Discharge is due to sinusitis Mainty maxillarysinisitis. ln this paper we are presenting one hundred cases of children suffering from secretary> otitis media and its relation with sinusitis. X-Rays of the sinuses were taken in all these patients. Patients in whom films showed maxillary sinusitis Antrim washout were carried out. Abnormal X-Rays were found in 60% of the patients. There was definite improvement in the middle ear disease when the sinus infection was treated. KEY WORDS Max Sinusitis, secretary otitis media.